The relationship of physical balance in the utilization of pelleted and nonpelleted rations for lambs. - Bell, T.D.; Richardson, D.; Cox, R.F.; Needham, J.W. (Kansas Agricultural Experiment Station, 2011)
Lamb-fattening rations varying in proportions of roughages to concentrate have been studied in this project several years. In recent years much interest has been shown by commercial lamb feeders in completely pelleted rations, and for the past three years this project has been designed to study the effect of pelleted and nonpelleted rations of varying proportions of roughages and concentrate upon feed-lot performance and feed efficiency.
Keywords: Sheep; Pelleted ration; Nonpelleted ration; Performance; Feed efficiency